Pengaruh Strategi Diferensiasi Produk dan Promosi Terhadap Minat Beli Konsumen Pada Usaha Kue Wawa Di Semparuk - Rahman, Rahman; Alexandro, Rinto (Universitas Pendidikan Ganesha, 2024)
This research aimed at investigating the effect of product differentiation strategies and promotions on consumer buying interest in the wawa cake business in semparuk. This research is quantitative research. This type of research is field research (field research) conducted by direct observation of the object under study to obtain appropriate data. The population in the study were all consumers of kue wawa semparuk. The sample in this study was carried out using a purposive sampling technique with random sampling, totaling 30 respondents. The results of this study indicate that the variables of product differentiation and promotion have a positive and significant effect on consumer buying interest. The results of the F test (simultaneous) are 8.740, and the coefficient of determination is 0.393, meaning that the results above have the influence of variables XI and X2 together or simultaneously on variable Y by 39.3%, and the remaining 60.7% is influenced by other factors outside the variables that researchers do.